Perceived Religious Social Support in Faith Communities for Caregivers of Persons Living with Dementia - Garrison, Brianna; Myers, Dennis; Parrish, Danielle; Oxhandler, Holly (Journal of Gerontological Social Work, 2025)
Keywords: Dementia; Faith; Gerontology; Medicine; Psychology; Psychotherapist; Social support; caregiver; dept.swk; faith community; peer-reviewed; social determinants of health; social support

The Impact of Spirituality and Religious Practice on Senior Living Leader Career Resilience - Myers, Dennis R.; Rogers, Robin K.; Garrison, Brianna V.; Singletary, Jon E.; Groce, Haley (Journal of Applied Gerontology, 2022)
Experienced senior living leaders (SLLs) report the impact of spirituality and religious practice on SLL role adaptation and continuation. The sample included 18 SLLs in 18 skilled care settings representing public, non-profit, and for-profit types of incorporation, with oversampling of for-profit facilities. The average years of SLL experience was 24 years. In-depth interviews were examined through a thematic analysis approach using Excel software. Seventy-eight percent described how a higher power, religious beliefs, and faith practices were associated with their role. Their narratives revealed three major themes: Frame (calling and pre-dispositional spiritual beliefs and religious practices), Role Performance (how spirituality informed SLL administrative practice), and Benefits (perceived rewards of adherence to spiritual beliefs and practices). Further analysis of the three themes produced codes that added greater specification for each theme. Implications provided for normalizing the spirituality and work-life intersect and infusing ethical integration of spirituality and work-life in SLL educational programs.
Keywords: adminstration; career resilience; dept.swk; faith and work; peer-reviewed; religious practices; skilled care; spirituality